The Importance of Program Evaluation in Overseeing the Successful Achievement of the National Development Agenda - Eko Riadi, Antonius Susilo (Universitas Syiah Kuala, 2023)
In order to prosper all Indonesian people, the President set seven national development agendas which in 2023 will be implemented through 84 priority programs/major projects spread across a number of Ministries/Institutions (K/L). The distribution of the program poses risks in terms of the relevance of the K / L program to the President's program, the effectiveness and efficiency of program achievement, as well as the impact of the program on the community and the sustainability of the program in the future. The purpose of the study is to broaden the horizons of stakeholders in K/L, including the Government Internal Supervision Apparatus (APIP) on the importance of program evaluation to ensure program success, and provide alternative program evaluation models that are relevant and appropriate to program characteristics. The study method is carried out through literature studies related to understanding of development plans, program / project design, program evaluation approaches / models, as well as analyzing and comparing various approaches / program evaluation models. Important results of this study include program evaluation is an important tool for every K / L to ensure that the program has been implemented to achieve the target outputs and outcomes that have been set. Value-added program evaluations are those that not only assess program outcomes or accountability, but also identify ways to improve the programs being evaluated. The Program Evaluation approach developed by the Asian Development Bank is an alternative model that in its design will evaluate the